HUBUNGAN KEPATUHAN MINUM ANTIRETROVIRAL DENGAN KUALITAS HIDUP PASIEN HIV/AIDS DI POLIKLINIK MAWAR RSUD KOLONEL ABUNDJANI BANGKO - Esti, Amira; Yolanda, Mona; Epida, Marta (Ensiklopedia of Journal, 2024)
HIV  is  a  type  of  virus  that  attacks  the  body's  immune  system.  Infection HIV  causes  damage  to  the  patient's  general  system.  System  glitches continued  immune  response  can  result  in  worsening  progression  of  HIV  infection become  AIDS.  This  can  be  controlled  with  antiretrovirals  (ARV). ARV  function  suppresses  the  replication  of  HIV  viruses  in  the  body,  thereby  improving  the  quality  of  life  of  HIV/ AIDS  patients.  This  research  aims  to  determine  compliance,  quality  of  life  and  the  relationship  between  compliance  and  quality  of  life  of  HIV/ AIDS  patients.  The  university  research  used  an  observational  analytical  design  with  a  cross- sectional  approach.  The  population  in  this  study  consisted  of  all  HIV/ AIDS  patients  who  received  ARV  therapy  at  Polklunk  Mawar,  Colonel  Abundjani  Bangko  Regional  Hospital  with  a  sample  of  39  people  using  a  total  sampling  technique.  Data  analysis  used  non- parametric  statistics  with  the  chi- square  test.  The  results  of  the  research  showed  that  35  respondents  (89.7%)  were  adherent  to  taking  ARVs,  34  respondents  (87.29)  had  good  quality  of  life.  valne=0.004  p0.05)  at  Poliklinik  Mawar  RSUD  Colonel  Abundjani  Bangko  Keywords : HIV/AIDS, adherence, quality of life, ARVs